İMAM SERAHSİ'NİN İÇİNDE YAŞADIĞI SİYASİ ORTAM VE HAPİS HAYATI - (:unkn) unknown (My University, 2013)
400/1009 tarihinde Horasan'ın Serahs şehri veya civarında doğan Şemsü'l-Eimme İmam es-Serahsî, ilk çocukluk yılları hariç ömrünün tamamını Buhâra, Özkent ve Fergana bölgesinde geçirmiştir. Zama-- nın en büyük âlimlerinden Şemsü'l-Eimme Halvânî ve es-Suğdî gibi önemli hocalardan ilim okumuş ve kendinden sonra gelen meşhur birçok âlime de hocalık yapmıştır. Ancak 466-480/1073--1087 yılları arasında 15 yıla yakın Özkent'te hapis hayatı yaşamıştır. Onun yaşa-- dığı dönemde bölgede Karahanlılar yönetimde bulunmaktaydı. Onu hapseden Karahanlı hükümdarı ise Şemsülmülk Il. Nasr Han olmuştur. Serahsî'nin niçin hapsedildiğine dair elimizde net bir bilgi olmamakla birlikte onun, devrin hükümdarına söylediği nasihat yollu bir söz veya ilahiyat alanında söylediği bir sözün muhalifleri tarafından çarpıtılarak hükümdara jurnallenmesi sonucu hapsedildiği tahmin edilmektedir. Ancak bu sözün ne olduğu kaynaklarda geçmemektedir. Serahsî, ağır hapis şartları altında 30 ciltlik muazzam eseri el-Mebsut başta olmak üzere diğer birçok eserini, kitap ve defterlerinden mahrum olduğu hal-- de hapiste öğrencilerine yazdırarak ilim dünyasının dikkatlerini üzeri-- ne çekmiştir. Son hapis yılları daha rahat bir mekânda geçen Serahsî 480/ 1087 yılında hapisten kurtulmuş ve ilmî çalışmalarını devam ettir-- diği erğana'nın Merginân şehrinde 483/ 1090 tarihinde vefat etmiştir.

Imam a1-Sarakhsi known as Shams al-Aimma (sun of Leaders) was born around Serahs city in 400/1009. Except for his early childhood, he spent almost his entire life in Buhâra, Ozkent and Fergana region. He gained knowledge from the greatest scholars of the time, such as Shams al-aimme Halvânî and al-Sugdi and he also taught many famous scholars. However, he was convicted as imprisoned for approximately 15 years in Ozkent between 466-480/1073-1087. The KaraHan tribe was in charge of the area during this period of his life. The name of the ruler of the KaraHans who imprisoned Imam al--Sarakhsi, was Shams al-Mulk ll. Nasr KHan. Although there is no specific information as to why as-Sarahsi was imprisoned, it is possible to say that he may have given some advice to the ruler of the era in the field of theology, and an expression within this advice may have been distorted by his opponents. Therefore, he most likely was imprisoned as result of these complaints. However, sources do not mention what this expression is. Although he was deprived of his books and notes under the terms of imprisonment, Sarakhsi has attracted the attention of the world of science by dictating number of his books for students to note in prison, especially his enormous well known 30-volume book, al-Mabsut.. Having received better conditions in prison in the later years of his imprisonment, Sarakhsi was released in 480/ 1087 and continued his scholarly work in the Merginan city where he passed away in 483/1090.
The Political environment which İmam Serahsi was in and his Prison life
Keywords: Din Bilimi